IMPLEMENTASI MASYARAKAT TERHADAP PENAFSIRAN SURAT AL-QADR - Mutiara Tri Julifa; Hafizzullah Hafizzullah (IAIN Batusangkar, 2020)
Departing from a custom that exists in the community of Bukit Putus in Linggo Sari Baganti Subdistrict, Pesisir Selatan District, namely the implementation of Lailatul Qadr circumcision prayer on every twenty-seventh night of the month of Ramadan. This research is called the Living Qur'an Study which is a qualitative field research, using descriptive analysis methods, with data collection techniques through interviews and documentation. The results of the study are the first, the public understands the Laylat al-Qadr prayer as circumcision prayer which is performed to welcome and respect the Laylat al-Qadr. Secondly, the public praying at the end of the twenty-seventh night after completing the evening prayer in congregation. Third, the implementation of the Prayers of Laylat al-Qadr by the community aims to get merit and forgiveness from God. Then the benefits felt by the community after performing lailatul qadr prayers include peace and tranquility of the heart.